Awareness of the mutual rights of parent - child view of Islamic teachings on reduce conflicts between parent - child - Atosa kalantar hormozi (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2014)
Aim: The present study was designed to investigate the effect of the mutual right of the parent-child from the perspective of Islamic teachings on reducing conflict between parent-child (mother-daughter) was carried out in teens. Methods: A quasi – experimental design with pre- test and post- test and a control group was employed. The population of this study was high school students of Gorgan city in the 2012-2013 academic year. The sample consisted of 24 patients (8 parents, 8 parents, 8 other children of the same parents as the test group and a control group of 8 children) who were randomly assigned to experimental and control groups In this paper, based on Islamic law, each member of the family together During the meeting the way a group of 6 experimental groups were trained separately. Assessment by Murray Conflict Tactics Scale - Form Strauss conflict with the parents of children in pre-test and post-test was given. In this study, ANCOVA was used to test group mean differences. Results: Results showed that parental rights awareness training - the child's parents and the children's reasoning skills, verbal aggression and conflict reduction in children had effective relationship with parents.